(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Early-life nutrition plays a crucial role in shaping long-term health outcomes, particularly in relation to obesity. While extensive research has explored dietary patterns and obesity risk, a knowledge gap remains regarding the precise mechanisms linking early nutritional exposures to long-term metabolic outcomes. This study aims to investigate the association between early childhood nutrition and the risk of obesity in later life.A systematic review and meta-analysis were conducted, examining longitudinal and cross-sectional studies that assess dietary intake, nutritional quality, and obesity prevalence from infancy through adolescence. Data from diverse populations were analyzed to identify trends and correlations, considering genetic, environmental, and socioeconomic factors. Findings indicate that excessive caloric intake, poor dietary diversity, and early introduction of highly processed foods contribute significantly to increased obesity risk. Additionally, breastfeeding and balanced nutrient intake in infancy appear to have a protective effect. The results suggest that early dietary habits influence metabolic programming, adiposity development, and long-term energy balance. Furthermore, early-life exposure to unhealthy dietary patterns can lead to alterations in gut microbiota, insulin resistance, and increased inflammatory markers, further predisposing individuals to obesity-related complications. Socioeconomic disparities in nutrition access also play a significant role, highlighting the need for targeted public health initiatives. These findings underscore the importance of early nutritional interventions in preventing obesity. Public health policies should emphasize parental education, promote breastfeeding, and encourage nutrient-rich diets in early childhood. Addressing early-life dietary patterns may serve as a critical strategy in mitigating the global obesity epidemic. Future research should focus on intervention strategies, long-term cohort studies, and the interplay between nutrition, genetics, and metabolic health.